Identifying perceived barriers to monitoring service quality among substance abuse treatment providers in South Africa - Myers-Franchi, Bronwyn; Petersen, Z.; Kader, R.; Koch, J.R.; Manderscheid, R.; Govender, R.; Parry, C.D.H. (2014)
Background: A performance measurement system is planned for South African substance abuse treatment services. Provider-level barriers to implementing these systems have been identified in the United States, but little is known about the nature of these barriers in South Africa. This study explored the willingness of South African substance abuse treatment providers' to adopt a performance measurement system and perceived barriers to monitoring service quality that would need to be addressed during system development.